Primary mucormycosis infection in the submandibular area after esthetic lipolytic injection in an immunocompetent patient: A case report - Hyeon Seok Kim; Woo Seob Kim; Han Koo Kim; Shin Hyuk Kang; Tae Jin Lee; Soon Auck Hong; Tae Hui Bae (Wolters Kluwer Medknow Publications, 2022)
As the popularity of injection lipolysis increases, several side effects of injection lipolysis have been reported. In this case, A 53-year-old woman visited our outpatient clinic with a new round-shaped protruding mass (size: 5.0 cm × 3.0 cm) in the submental area. The patient had received the injection lipolysis treatment before the visit. She had received injections in the submental area at 1-week intervals (i.e., 4, 5, and 6 weeks). We performed contrast-enhanced computed tomography of the neck for differential diagnosis and found a 5.0 cm × 3.7 cm × 2.1 cm rim-enhanced fluid-density lesion in the submental. Hence, surgical removal of the lesion was planned based on the diagnosis of unspecified complicated fluid collection. The removed mass was a 3.0 cm × 2.0 cm × 2.0 cm whitish fibrous tissue. Histological examination revealed mucormycosis infection. Although several side effects of lipolysis have been reported to date, mucormycosis infection in the submental area has not been reported before.